Birefringence-modulated total internal reflection in liquid crystal shells - Popov, Nikolay; Lagerwall, Jan P. F. (Frontiers in Soft Matter, 2022)
The combination of anisotropic boundary conditions and topological constraints acting on a spherical shell of nematic liquid crystal confined between aqueous phases gives rise to peculiar but well-defined configurations of the director field, and thus of the optic axis that defines the impact of the nematic birefringence. While the resulting optics of nematic shells has been extensively investigated in transmission, studies of the reflection behavior are scarce. Here we show that nematic shells exhibit specific light guiding paths mediated by birefringence-modulated total internal reflection (TIR) within the shell. With stabilizers promoting tangential boundary conditions, shells show immobile antipodal spots revealing the locations of maximum effective refractive index, but their intensity is modulated by the polarization of the illuminating light. With normal-aligning stabilizers, shells instead show bright arcs separated by dark spots, and these follow the rotation of the polarization of the illuminating light. Reflection polarizing microscopy thus offers a valuable complement to the more common characterization in transmission, adding data that can be helpful for accurately mapping out director fields in shells of any liquid crystal phase. Moreover, the TIR-mediated light guiding paths may offer interesting handles to localize photopolymerization of reactive liquid crystal shells or to dynamically modulate the response of light-triggered liquid crystal elastomer shell actuators.